Myocardial performance index in children with ?-thalassemia major - Suman, Rameshwar Lal; Sanadhya, Anuradha; Singh, Jaskaran; Meena, Pradeep (Indian Journal of Child Health, 2016)
Background: Cardiac complications are the major cause of mortality and morbidity in thalassemic children. Iron deposition in myocardium is the key factor leading to poor cardiac functions. Myocardial performance index (MPI) by echocardiography (ECHO) can be used for an early recognition of ventricular dysfunctions. Objectives: To assess the MPI in children with ?-thalassemia major and to establish their relationship with serum ferritin. Methods: Fifty-five children of Thalassemia major in age group of 4-20 years who were on regular blood transfusion and on oral iron chelators from thalassemia unit of tertiary hospital were enrolled. After blood transfusion, serum ferritin estimation was done. Two dimensional ECHO with color Doppler was done to estimate the cardiac functions and then MPI by various parameters was calculated. Results: Out of 55 children, most were in the age group of 4 to 8 years. Mean rate of blood transfusion in subjects was 157.01 ± 21.33 ml/kg/year and mean duration of chelation therapy was 2.34 ± 1.86 years. Mean serum ferritin of subjects was 2130 ± 859.5 ng/ml. Mean ejection fraction was 61 ± 6.2%. Mean MPI of subjects was 0.60 ± 0.14. The MPI was abnormal at all levels of more than 1000 ng/ml serum ferritin (p=0.001). There was a positive correlation between MPI and serum ferritin (Pearson’s bivariate correlation coefficient r=+0.93). Conclusion: In poorly chelated thalassemic children, MPI was abnormally high despite normal ejection fraction, which can be used as an early marker of ventricular dysfunction.